Pengaruh Aktiva Tetap, Hutang Jangka Panjang, dan Modal terhadap Laba Bersih Perusahaan Agribisnis Indeks LQ 45 yang Terdaftar di Bursa Efek Indonesia - PASMA SUARTIKA, IM.; SUARTANA, IW.; PUTRA DARMAWAN, DWI (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
Normal 0 false false false IN X-NONE X-NONE So far, the owners of capital are always keen to invest in the stock market , however not all companies listed on the stock exchange will have a big investor . This is partly due to price fluctuations , investors can also look at the future prospects of the company , does provide a substantial or not. As agribusiness companies listed on the Indonesia Stock Exchange Index 45 for LQ is still very slow progress compared to other companies , so investors are less keen to invest in the company , so the performance is rather low . The problem formulated in this study is a variable fixed assets , long-term debt and capital affect net income in the agribusiness firm LQ 45 index listed in the Indonesia Stock Exchange in 2007 until the year 2010 ?. The variable is the most dominant effect on net income in the agribusiness firm LQ 45 index listed in the Indonesia Stock Exchange in 2007 until the year 2010 ?. The purpose of this study was conducted to analyze and to determine the effect of variable fixed assets , long-term debt and equity to net income in the agribusiness firm LQ 45 index listed in the Indonesia Stock Exchange in 2007 until 2010 . And to determine the most dominant variable effect between fixed assets , long-term debt and equity to net income in the agribusiness firm LQ 45 index listed in the Indonesia Stock Exchange in 2007 until 2010 . Xi variables jointly influence the variables Y1 at 72.89 %, which means that the fluctuations or variations amounted to 72.89 % variable Y1 influenced or caused by variable Xi together , and the remaining 27.11% or (1 - R2 = 1-72 , 89% ) were caused by other factors or other variables . Partially only 2 independent variables Xi which significantly affect the dependent variable Y1 fixed assets ( X1) and capital ( X3), and other independent variables Xi (loans ) have not significant ( p> 0.05) to the dependent variable Y1 free . This means that each additional 1.00 USD fixed assets ( X1) will result in a decrease in net income ( Y1) significantly by Rp 0.309 , and any additional capital to Rp 1.00 ( X3) will lead to an increase in net income ( Y1) is real Rp 0.528 . The independent variable X3 is the most dominant effect on the dependent variable Y1 with a value of 8.864 with a chance F-hitung 0.005 ( very real). The two dominant variables are X1 F-hitung value of 47.541 with a chance of 0.000 ( very real). /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-ansi-language:IN; mso-fareast-language:EN-US;}